The event as a referent of the concept UKRAINE in the English publicist discourse - Mudrachenko, T.B. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
The article deals with events as referents of the concept UKRAINE in the modern English publicist discourse. Events are viewed as complex situations which reflect deep and surface interlinks between actors, their characteristics, actions and relations. The events are qualified literally and metaphorically, explicitly and implicitly.
Keywords: an event; an actor; explicit and implicit; literal and metaphoric qualification